EFEKTIVITAS DONEPEZIL TERHADAP FUNGSI KOGNITIF PASIEN TUMOR INTRAKRANIAL PASCAOPERASI - Yusril Harun; Yunni Diansari; Selly Marisdina; Yuli Felistia (PERDOSNI, 2020)
EFFECTIVITY OF DONEPEZIL IN COGNITIVE FUNCTION OFPOSTOPERATIVE INTRACRANIAL TUMOUR PATIENTSABSTRACTIntroduction: There is still a lack of effective therapy in improving cognitive dysfunction in intracranial tumour patients after surgery. Donepezil is an acetylcholinesterase inhibitor that has been a therapy of Alzheimer's disease and has a significant effect on improving cognitive function.Aim: To determine the effectiveness of donepezil on cognitive function in patients with postoperative intracranial tumours.Methods: A clinical, randomized, double-blind study was conducted on postoperative intracranial tumour patients categorized into two groups (donepezil and placebo). The intervention was donepezil 5mg once a day for three months. For assessment of cognitive function, Mini-Mental State Examination (MMSE) and Indonesian Version of Montreal Cognitive Assessment (MoCA-Ina) was checked at weeks 0 (baseline), 4 (end of the first month), 8 (end of the second month), and 12 (end of the third month). Data were analyzed using SPSS 22.Results: Twenty patients, equally distributed in two groups, were included in the study. Compared to baseline, MMSE and MoCA-Ina scores in the donepezil group increased significantly on the second and third month (p<0.001). There was a remarkable difference in cognitive function between two groups on the third month based on MMSE and MoCA-Ina scores (p=0.027 and 0.024, respectively). At post-intervention, orientation and recalldomain in MMSE showed marked improvement, while visuospatial and delayed recall domain experienced as well in MoCA-Ina. There were no significant side effects of donepezil.Discussion: This results can be considered for administration of donepezil in patients with intracranial tumours after surgery with impaired cognitive function.Keywords: Cognitive function, donepezil, intracranial tumour, MMSE, MoCA-Ina, surgeryABSTRAKPendahuluan: Saat ini belum ada terapi yang efektif dalam memperbaiki gangguan fungsi kognitif pada pasien tumor intrakranial pascaoperasi. Donepezil merupakan inhibitor asetilkolinesterase yang telah menjadi terapi dari penyakit Alzheimer dan memiliki efek yang bermakna dalam memperbaiki fungsi kognitif.Tujuan: Mengetahui efektivitas donepezil terhadap fungsi kognitif pasien tumor intrakranial pascaoperasi.Metode: Studi uji klinis, acak, tersamar ganda dilakukan pada pasien tumor intrakranial pascaoperasi dengan gangguan kognitif yang terbagi dalam dua kelompok (donepezil dan plasebo). Intervensi yang dilakukan berupa pemberian donepezil 5mg satu kali sehari selama 3 bulan. Evaluasi fungsi kognitif menggunakan Mini Mental State Examination (MMSE) dan Montreal Cognitive Assessment Versi Indonesia (MoCA-Ina) pada minggu 0 (awal), 4 (akhir bulan ke-1), 8 (akhir bulan ke-2), dan 12 (akhir bulan ke-2). Data dianalisis menggunakan perangkat SPSS 22.Hasil: Sebanyak 20 subjek yang terbagi sama pada dua kelompok diikutsertakan pada penelitian ini. Dibandingkan dengan kondisi awal, nilai MMSE dan MoCA-Ina pada kelompok donepezil meningkat secara signifikan pada bulan ke-2 dan ke-3 (p<0,001). Terdapat perbedaan bermakna fungsi kognitif antara kelompok terapi dengan placebo pada bulan ke-3 berdasarkan nilai MMSE (p=0,027) dan MoCA-Ina (p=0,024). Domain pada MMSE yang mengalami perbaikan bermakna setelah terapi donepezil adalah orientasi dan recall, sedangkan pada MoCA-Ina adalah domain visuospasial dan delayed recall. Tidak didapatkan efek samping donepezil yang bermakna.Diskusi: Hasil penelitian ini dapat menjadi pertimbangan dalam pemberian donepezil pada pasien dengan tumor intrakranial pascaoperasi yang memiliki gangguan fungsi kognitif.Kata kunci: Donepezil, fungsi kognitif, MMSE, MoCA-Ina, operasi, tumor intrakranial